Managing Surges in Capital Inflows: The Philippines Case - Mario B. Lamberte (Philippine Institute for Development Studies (PIDS), 1994)
The Philippines is one of the countries in Southeast Asia that has experienced massive capital inflows. Being a latecomer in this arena, it can avoid the undesirable effects of these inflows by drawing lessons from the experiences of Latin American and Other Asian countries. This paper provides a background and characteristics of capital inflows to developing countries and discusses the issues associated with it. Analysis shows that full sterilization deprives the country of higher investment and growth associated with foreign exchange inflows.
Keywords: 330; competition policy; foreign investment; sterilization; capital flows; capital account